1/2 + 1/3 + 5/12 =
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{2}{5}+\dfrac{2}{3}+\dfrac{2}{4}\)
= \(\dfrac{24}{60}\) + \(\dfrac{40}{60}\) + \(\dfrac{30}{60}\)
= \(\dfrac{64}{60}\) + \(\dfrac{30}{60}\)
= \(\dfrac{47}{30}\)
\(\dfrac{2}{6}+\dfrac{3}{12}\)
= \(\dfrac{4}{12}\) + \(\dfrac{3}{12}\)
= \(\dfrac{7}{12}\)
\(\dfrac{5}{6}\) + \(\dfrac{1}{3}\)
= \(\dfrac{5}{6}\) + \(\dfrac{2}{6}\)
= \(\dfrac{7}{6}\)
\(\dfrac{1}{3}\) + \(\dfrac{5}{12}\) + \(\dfrac{5}{6}\)
= \(\dfrac{4}{12}\) + \(\dfrac{5}{12}\) + \(\dfrac{10}{12}\)
= \(\dfrac{9}{12}\) + \(\dfrac{10}{12}\)
= \(\dfrac{19}{12}\)
\(\dfrac{5}{8}\) + \(\dfrac{4}{7}\)
= \(\dfrac{35}{56}\) + \(\dfrac{32}{56}\)
= \(\dfrac{67}{56}\)
\(\dfrac{7}{3}\) + \(\dfrac{8}{7}\)
= \(\dfrac{49}{21}\) + \(\dfrac{24}{21}\)
= \(\dfrac{73}{21}\)
\(\dfrac{1}{5}+\dfrac{5}{35}\)
= \(\dfrac{7}{35}\) + \(\dfrac{5}{35}\)
= \(\dfrac{12}{35}\)
Bài giải:
Câu 1: a, \(\left(-2\right).4.5.38.\left(-25\right)\)
\(=\left[\left(-2\right).5\right].\left[4.\left(-25\right)\right].38\)
\(=\left(-10\right).\left(-100\right).38\)
\(=1000.38=38000\)
b,\(\frac{1}{3}+\frac{3}{8}-\frac{7}{12}\)
\(=\left(\frac{1}{3}+\frac{3}{8}\right)-\frac{7}{12}\)
\(=\frac{17}{24}-\frac{7}{12}=\frac{1}{8}\)
c, \(\frac{-5}{8}.\frac{5}{12}+\frac{-5}{8}.\frac{7}{12}+2\frac{1}{8}\)
\(=\frac{-5}{8}.\left(\frac{5}{12}+\frac{7}{12}\right)+\frac{17}{8}\)
\(=\frac{-5}{8}.1+\frac{17}{8}\)
\(=\frac{3}{2}\)
Câu 2: a, \(x-\frac{2}{5}=0,24\)
\(x-0,4=0,24\)
\(x=0,24+0,4\)
\(\Rightarrow x=0,64\left(\frac{16}{25}\right)\)
b,\(\frac{2}{3}.x+\frac{1}{12}=\frac{1}{10}\)
\(\frac{2}{3}.x=\frac{1}{10}-\frac{1}{12}\)
\(\frac{2}{3}.x=\frac{1}{60}\)
\(x=\frac{1}{60}:\frac{2}{3}\)
\(\Rightarrow x=\frac{1}{40}\)
c, \(\left(3\frac{1}{2}-2x\right).1\frac{1}{3}=7\frac{1}{3}\)
\(\frac{7}{2}-2x=\frac{22}{3}:\frac{4}{3}\)
\(\frac{7}{2}-2x=\frac{11}{2}\)
\(2x=\frac{7}{2}-\frac{11}{2}\)
\(2x=-2\)
\(\Rightarrow x=-2:2\)
\(x=-1\)
Bài làm
1.
11 3/13 - ( 2 4/7 + 5 3/13 )
= 11 3/13 - 2 4/7 - 5 3/13
= ( 11 3/13 - 5 3/13 ) - 2 4/7
= { (11 - 5 ) . ( 3/13 - 3/13 ) } - 2 4/7
= ( 6 . 0 ) - 2 4/7
= 0 - 2 4/7
= 2 4/7
= 18/7
2 .
19 5/8 : 7/12 + ( -15 1/4) : 7/12
= { 19 5/8 + ( -15 1/4 ) } : 7/12
= [ { 19 + ( - 15) } . ( 5/8 + 1/4 ) ] : 7/12
= { 4 . ( 5/8 + 2/8 ) } : 7/12
= ( 4 . 7/8 ) : 7/12
= 1.7/2 : 7/12
= 7/2 : 7/12
= 7/2 . 12/7
= 1.1/6.1
= 1/6
3 .
2/5 . 1/3 - 2 2/15 : 1/5 + 3/5 . 1/3
= 1/3 . ( 2/5 + 3/5 ) - 2 2/15 : 1/5
= 1/3 . 5/5 - 32/15 . 5/1
= 1/3 . 1 - 32.1/3.1
= 1/3 - 32/3
= -31/3
4 .
( 3 1/3 + 2,5 ) : ( 3 1/6 - 4 1/5 ) - 11/31
= ( 10/3 + 25/10 ) : { ( 3 - 4 ) . ( 1/6 - 1/5 ) - 11/31
= ( 10/3 + 5/2 ) : { (-1) . ( 5/30 - 6/30 ) } - 11/31
= ( 20/6 + 15/6 ) : { (-1) . (-1)/30 } - 11/31
= 35/6 : 1/30 - 11/31
= 35/6 . 30/1 - 11/31
= 35.5/1.1 - 11/31
= 175 - 11/31
= 5425/31 - 11/31
= 5414/31
5.
75% - 1 1/5 + 0,5 : 5/12 - (-1/2)2
= 75/100 - 6/5 + 5/12 - 1/4
= 3/4 - 6/5 + 5/12 - 1/4
= ( 3/4 - 1/4 ) + ( 5/12 - 6/5 )
= 2/4 + ( 25/60 - 30/60 )
= 1/2 + (-5)/60
= 1/2 + (-1)/12
= 6/12 + (-1)/12
= 5/12
Đúng thì k cho mình nha !
1)
11 3/13 - ( 2 4/7 + 5 3/13 )
= 11 3/13 - 2 4/7 - 5 3/13
= ( 11 3/13 - 5 3/13 ) - 2 4/7
= { (11 - 5 ) . ( 3/13 - 3/13 ) } - 2 4/7
= ( 6 . 0 ) - 2 4/7
= 0 - 2 4/7
= 2 4/7
= 18/7
2 )
19 5/8 : 7/12 + ( -15 1/4) : 7/12
= { 19 5/8 + ( -15 1/4 ) } : 7/12
= [ { 19 + ( - 15) } . ( 5/8 + 1/4 ) ] : 7/12
= { 4 . ( 5/8 + 2/8 ) } : 7/12
= ( 4 . 7/8 ) : 7/12
= 1.7/2 : 7/12
= 7/2 : 7/12
= 7/2 . 12/7
= 1.1/6.1
= 1/6
3 )
2/5 . 1/3 - 2 2/15 : 1/5 + 3/5 . 1/3
= 1/3 . ( 2/5 + 3/5 ) - 2 2/15 : 1/5
= 1/3 . 5/5 - 32/15 . 5/1
= 1/3 . 1 - 32.1/3.1
= 1/3 - 32/3
= -31/3
4 )
( 3 1/3 + 2,5 ) : ( 3 1/6 - 4 1/5 ) - 11/31
= ( 10/3 + 25/10 ) : { ( 3 - 4 ) . ( 1/6 - 1/5 ) - 11/31
= ( 10/3 + 5/2 ) : { (-1) . ( 5/30 - 6/30 ) } - 11/31
= ( 20/6 + 15/6 ) : { (-1) . (-1)/30 } - 11/31
= 35/6 : 1/30 - 11/31
= 35/6 . 30/1 - 11/31
= 35.5/1.1 - 11/31
= 175 - 11/31
= 5425/31 - 11/31
= 5414/31
5)
75% - 1 1/5 + 0,5 : 5/12 - (-1/2)2
= 75/100 - 6/5 + 5/12 - 1/4
= 3/4 - 6/5 + 5/12 - 1/4
= ( 3/4 - 1/4 ) + ( 5/12 - 6/5 )
= 2/4 + ( 25/60 - 30/60 )
= 1/2 + (-5)/60
= 1/2 + (-1)/12
= 6/12 + (-1)/12
= 5/12
\(a,\left(\dfrac{2}{3}-\dfrac{1}{4}+\dfrac{5}{11}\right):\left(\dfrac{5}{12}+1-\dfrac{7}{11}\right)\)
\(=\dfrac{115}{132}:\dfrac{103}{132}=\dfrac{115}{132}.\dfrac{132}{103}=\dfrac{115}{103}\)
\(b,\left(-\dfrac{1}{2}\right)^2-\left(-2\right)^2-5^0\)
\(=\dfrac{1}{4}-4-1=-\dfrac{19}{4}\)
\(c,12\dfrac{1}{3}-\dfrac{5}{7}:\left(24-23\dfrac{5}{7}\right)\)
\(=\dfrac{37}{3}-\dfrac{5}{7}.\dfrac{2}{7}=\dfrac{37}{3}-\dfrac{10}{49}=\dfrac{1783}{147}\)
bài 1:
a) 1/3x=-5/3
x=-5
b) x+12/5=37/15
x=1/15
c) x-1/7=-36/7
x=-5
d) 3x-1/2=0
3x=1/2
x=1/6
e) 2/5+x=1/4
x=-3/20
1/2 + 1/3 + 5/12 = 5/4
học tốt
\(\frac{1}{2}+\frac{1}{3}+\frac{5}{12}\)
\(=\frac{6}{12}+\frac{4}{12}+\frac{5}{12}\)
\(=\frac{10}{12}+\frac{5}{12}\)
\(=\frac{5}{4}\)